Moderating Effect of Perceived Organizational Support on the Relationship Between Employee Performance and Its Determinants: A Case of Entrepreneurial Firms in UAE - Ahli, Reem; Hilmi, Mohd Faiz; Abudaqa, Anas (Aptisi Transactions On Technopreneurship (ATT), 2024)
Considering the organizational success, employees performance has been accepted as among the fundamental role players. However, several organizational factors like abusive supervision, job stress, turnover intention, and agile leadership have been accepted as among the most critical determinants of such performance outcomes. The objective of this study is to assess the moderating effect of perceived organizational support on the relationships among abusive supervision, job stress, turnover intention, and agile leadership on employee performance in public firms in the UAE. A valid sample of 211 respondents from the public sector firms in UAE has been collected. The present study applies the measurement model and structural model assessment using the Smart PLS version 4. The findings confirm the presence of the internal consistency reliability, convergent validity, and discriminant validity of the latent constructs when examined through their relative items. Moreover, the structural equation modelling reveals that there is a significant impact of agile leadership, abusive supervision, and job stress on the employee performance among the public firms of UAE. Additionally, the findings state that there is a significant moderating effect of perceived organizational support on the relationship between agile leadership and employee performance, between abusive supervision and employee performance, and between job stress and employee performance, respectively. Based upon the given findings, several policy implications have also been suggested for the policymakers specifically at the public firms in UAE.